Current challenges for cancer vaccine adjuvant development - William S. Bowen; Abhishek K. Svrivastava; Lalit Batra; Hampartsoum Barsoumian; Haval Shirwan (Taylor & Francis Group, 2018)
Introduction: Although much progress has been made in the last decade(s) toward development of effective cancer vaccines, there are still important obstacles to therapeutic successes. New generations of cancer vaccines will benefit from a combination adjuvant approach that targets multiple branches of the immune response. Areas covered: Herein we describe how combinatorial adjuvant strategies can help overcome important obstacles to cancer vaccine development, including antigen immunogenicity and tumor immune suppression. Tumor antigens may be both tolerogenic and may utilize active mechanisms to suppress host immunity, including downregulation of MHC molecules to evade recognition and upregulation of immune inhibitory receptors, to subvert an effective immune response. The current cancer vaccine literature was surveyed to identify advancements in the understanding of the biological mechanisms underlying poor antigen immunogenicity and tumor immune evasion, as well as adjuvant strategies designed to overcome them. Expert commentary: Poor immunogenicity of tumor antigens and tumor immune evasion mechanisms make the design of cancer vaccines challenging. Growing understanding of the tumor microenvironment and associated immune responses indicate the importance of augmenting not only the effector response, but also overcoming the endogenous regulatory response and tumor evasion mechanisms. Therefore, new vaccines will benefit from multi-adjuvanted approaches that simultaneously stimulate immunity while preventing inhibition.